Structural and Magnetic Properties of La2/3D1/3MnO3 (D = Ca, Sr, Ba) Manganites Prepared By Ball Milling - Sami Mahmood; Haneen Badran; Eman Al-Hwaitat; Ibrahim Bsoul; Rola Bqaeen (Jordan Journal of Physics, 2025)
In this research, we report on the synthesis and characterization of La0.67Ca0.33MnO3 (LCMO), La0.67Ba0.33MnO3 (LBMO), and La0.67Sr0.33MnO3 (LSMO) perovskites. Precursor powders for the perovskite samples were prepared using ball mailing technique. The resulting powder was pressed into disks which were subsequently sintered at 1000º C for 2h. The structural characteristics of the prepared samples were investigated using X-ray diffraction (XRD) and scanning electron microscope (SEM), and the magnetic properties were investigated using vibrating sample magnetometry (VSM). XRD pattern of LCMO sample revealed a pure perovskite phase with Pnma space group, while the pattern of LSMO sample revealed a pure perovskite with space group. XRD pattern of LBMO sample, however, demonstrated the presence of a major perovskite phase with symmetry, together with a secondary BaMnO3 phase. This secondary phase disappeared upon sintering LBMO at a higher temperature of 1100º C. Isothermal magnetic measurements and thermomagnetic curves revealed that LCMO was paramagnetic at room temperature. However, LSMO exhibited soft ferromagnetic behavior at room temperature, with Tc = 380 K and Ms = 50.9 emu/g. Also, LBMO sample sintered at 1000º C exhibited soft ferromagnetic behavior at room temperature, with Curie temperature Tc = 343 K and a rather low saturation magnetization of Ms = 30.7 emu/g. The higher sintering temperature of LBMO compound resulted in a significant increase of the saturation magnetization to 50.8 emu/g for the sample sintered at 1100º C. Keywords: Perovskites, Structural properties, Magnetic properties, Thermomagnetic curves.